Quality and Customer Loyalty in Islamic Banks: Religiosity as a Moderator by using Andrew Hayes model - Shahzad, Mohsin; Malik, Muhammad Shaukat; Irfan, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2019)
The preservation of desired levels of service quality, product quality and awareness is domineering for firms to stay competitive. Islamic banking system of Pakistan is more growing and become popular that provide the products with the premises of Sharia compliance, but there is problem in this sector is lack of knowledge about the products. Findings relay on data collected through surveys of 300 customers of south Punjab Islamic banking sector. Through the respondent’s opinions, our study revealed that service quality and product quality have significantly relationship with customer satisfaction and loyalty. There is shortage of familiarity about Islamic banking products to the customers and this caused to low satisfaction. Proper information is highly required in this sector to create patronize customers. More findings exposed that customer satisfaction positively indicates to customer loyalty and by using the Andrew Hayes method religiosity only moderates between service quality and customer satisfaction because religiosity is not the sole factor to satisfy the customers without proper information system about products. To maintain the competitive edge there is highly required proper brochures system in every branch with easily access to the customers for more convenience.